THE ANCIENT GREEK PRONOUN Ό, Ή, TO IN THE MYCENAEAN PERIOD (Annual of the Faculty of Philosophy in Skopje, 2012)
On the Mycenaean tablets there are several forms corresponding to the Post-Mycenaean forms of the pronoun ό, ή, το. The comparison of the Mycenaean forms with the Post-Mycenaean Greek forms shows that in the Mycenaean period this pronoun was used not only as a demonstrative pronoun, but also as a 3-rd person personal pronoun. The comparison also shows specific features in the inflexion. On one hand Mycenaean evidence confirms that forms like τοίο, τοϊσι are old and on the other hand it reveals different forms, such as the dative-locative or instrumental-ablative singular forms to-e, to-me.
Keywords: DEMONSTRATIVE PRONOUNS; PRONOMINAL INFLEXION; MYCENAEAN GREEK